Precursors of atherosclerotic and hypertensive diseases among adolescents in Addis Ababa, Ethiopia. - Kebede, D. (World Health Organization, 1993)
The present study measured the prevalence of the precursors of atherosclerosis among 519 adolescents selected from high-school students in Addis Ababa. Also assessed was their knowledge about these precursors and about the hazards of smoking and of heavy alcohol consumption. A total of 13.8% of the adolescents smoked, 11.6% had a sedentary lifestyle, 9.2% consumed alcohol heavily, 14.1% were obese, 30.3% had one risk factor, and 4.4% had two risk factors for atherosclerosis. Altogether, 58% had inadequate knowledge about the precursors of atherosclerosis, and 62% and 51.4%, respectively, had inadequate knowledge about the hazards of smoking and of consuming alcohol. High-risk behaviours were positively associated with upper-income families and inadequate knowledge about the precursors of atherosclerosis. A substantial proportion of adolescents in Addis Ababa therefore exhibit the precursors of atherosclerotic and hypertensive diseases. Further, similar studies should be carried out in other Ethiopian cities, and the Ministries of Health and Education should give due attention to the primary prevention of these diseases and formulate plans for appropriate actions.